Analysis of Performance Appraisal of State Civil Apparatus in the Regional Office of Education of North Sulawesi Province - Recky H. E. Sendouw; Elvis M. C. Lumingkewas; Brain F. Supit; Pingkan M. M. Kapojos (Technium Social Sciences Journal, 2023)
The research objective was to examine how the performance evaluation of the state civil apparatus was carried out at the Education Office of North Sulawesi Province. The type and method of research is qualitative field research. Data collection techniques based on observation, interviews, and documentation. FromThe author’s observations led to the conclusion that the performance assessment of the State Civil Apparatus at the North Sulawesi Provincial Education Office with service quality indicators was carried out very well. However, indicators of timeliness that are not implemented properly indicate that regular performance appraisals are needed to improve the performance of the state civil apparatus in the future.